The Science of Emotion: Mind, Body, and Culture - Cecilea Mun (Philosophies, 2022)
In this paper, I give readers an idea of what some scholars are interested in, what I found interesting, and what may be of future interest in the philosophy of emotion. I begin with a brief overview of the general topics of interests in the philosophy of emotion. I then discuss what I believe to be some of the most interesting topics in the contemporary discourse, including questions about how philosophy can inform the science of emotion, responses to aspects of the mind–body problem, and concerns about perception, cognition, and emotion, along with questions about the place of 4E approaches and meta-semantic pluraliste approaches in the embodied cognitive tradition. I also discuss the natural kind–social construction debate in the philosophy of emotion, the emerging field of cultural evolution, the import of a dual-inheritance theory in this emerging field, and I propose a possible way to integrate the frameworks of dual-inheritance theory and meta-semantic pluralisme to demonstrate at least one way in which the philosophy of emotion can contribute to the emerging field of cultural evolution. I conclude with a brief summary of this paper and note at least one significant implication of my proposal for the natural kind–social construction debate in the philosophy of emotion.